Entertaining German culture contemporary transnational television and film - Ehrig, Stephan 1986-; Schaper, Benjamin 1988-; Ward, Elizabeth (Berghahn, 2023)
Audiences for contemporary German film and television are becoming increasingly transnational, and depictions of German cultural history are moving beyond the typical post-war focus on German's problematic past. This book explores this radical shift, building on recent research into transnational culture to argue that a new process of internal and external cultural reabsorption is taking place through areas of mutually assimilating cultural exchange such as streaming services, an increasingly international film market, and the import and export of Anglo-American media formats
Keywords: Motion pictures / Germany / History / 21st century; Motion pictures / Appreciation / Germany; Motion pictures / Production and direction / Technological innovations / Germany; Television series / Germany / History / 21st century; Television series / Germany / Appreciation; Television series / Technological innovations / Germany; Transnationalism in motion pictures; Germany / In motion pictures; Motion pictures; Motion pictures / Appreciation; Television series; Germany; 2000-2099; History; Aufsatzsammlung